The impact of intellectual capital on stock price with financial performance as intervening variable of manufacturing listed in Indonesia Stock Exchange period 2008 2012 - Andry Kurniawan (The Indonesian Accounting Review, 2014)
Intellectual capital (IC) is a platform for companies to be more competitive. The principal purpose of this research is to investigate relationship between Intellectual Capital (VAICTM) and stock price through financial performance at manufacturing companies that listed in Indonesia Stock Exchange during 2008-2012. This research is conducted by testing effect of VAICTM as independent variable to stock price as dependent variable, and financial performance (ROE and EPS) as intervening variable. Samples of this research are annual report and financial statements for manufacturing companies that listed in Indonesia Stock Exchange during 2008-2012. Samples were selected by using purposive sampling method and 372 manufacturing companies were able to fulfill the criteria used as sample. The research data is analyzed using path analysis method. The results of regression analysis show that VAICTM have no effect on ROEand EPS. ROE has no effect on stock price and EPS has an effect on stock price. This research also finds that VAICTM has no effect to stock price. The last result is ROE and EPS not a mediator variable because not able to mediate the relationship between VAICTM and stock price.